Letter from Carl D. Duncan to Patricia Whiting, dated 1964-10-19 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Letter addressed to the Manager of Spartan Rental services regarding study facilities for several international African students from Guinea and Upper Volta with a handwritten note to Patricia Whiting indicating that study facilities will be provided.